Day 1 Mon, December 10, 2018 2018
DOI: 10.2118/193770-ms
|View full text |Cite
|
Sign up to set email alerts
|

Non-Equilibrium Interactions Between Heavy Oil and Liquid Propane

Abstract: In this study, we use a custom-designed visual cell to investigate nonequilibrium interactions between liquid propane (C3(1)) and a heavy oil sample (7.2°API) at 55°C. The heavy oil sample is taken from Clearwater Formation located in Western Canadian Sedimentary Basin (WCSB). We inject C3(1) into the visual cell containing the heavy oil sample (pressure buildup process) and allow the injected C3(1) to interact with the oil sample (soaking process). After the pressure buildup process, we observe three phases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Furthermore, they concluded that the color of C 3,L would be darker if the concentration of heavier hydrocarbon components in C 3,L increases. Yassin et al studied the nonequilibrium interactions between CO 2 and oil and their findings about the formation of a uniform dark liquid phase are consistent with the findings of Athar et al and Eghbali et al Further detail about the findings of Yassin et al can be found elsewhere . Based on our observations and the reviewed literature, it can be concluded that the change in the color of propane from transparent to mild yellow during depletion in Test 1 and the formation of a yellow liquid phase in Test 2 and a dark liquid phase in Test 3 indicate the extraction of bitumen components by propane.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, they concluded that the color of C 3,L would be darker if the concentration of heavier hydrocarbon components in C 3,L increases. Yassin et al studied the nonequilibrium interactions between CO 2 and oil and their findings about the formation of a uniform dark liquid phase are consistent with the findings of Athar et al and Eghbali et al Further detail about the findings of Yassin et al can be found elsewhere . Based on our observations and the reviewed literature, it can be concluded that the change in the color of propane from transparent to mild yellow during depletion in Test 1 and the formation of a yellow liquid phase in Test 2 and a dark liquid phase in Test 3 indicate the extraction of bitumen components by propane.…”
Section: Resultssupporting
confidence: 68%
“…In this regard, the extraction mechanism in heavy oil and bitumen systems is less significant than that in the light oil . Athar et al evaluated the nonequilibrium interactions between propane and heavy oil using a visualization cell. , Based on their observations, propane may be mixed with bitumen as a result of extracting and draining flows. Ahadi and Torabi suggested that for a multiple-cycle CSI, the contribution of the extraction mechanism in heavy oil recovery is lower for the subsequent cycles.…”
Section: Introductionmentioning
confidence: 99%